TEACHER STRATEGY IN GROWING INTERPERSONAL INTELLIGENCE OF CHILDREN DRUM BAND PARTICIPANTS - Pramudita, Widya Evin; Nugroho, Agustinus Arum Eka (Jurusan PGPAUD FIP UNNES, 2019)
This study aims to describe the teacher's strategy in growing interpersonal intelligence of children participating in the drum band at  Hj. Isriati Baiturrahman 2 Semarang Kindergarten School. The method used in this research is a qualitative method with a case study approach. Research location in  Hj. Isriati Baiturrahman 2 Semarang  Kindergarten School. Research subjects that are the source of data such as teacher, trainer, and child. Data collection of techniques in this study include: observation, interviews, and documentation. Data analysis of techniques used are: Interactive. Based on data analysis, it can be concluded that the teacher's strategy in growing interpersonal intelligence of the children of drum band participants is through habituation. The teachers educate, teach, direct, stimulate, motivate, and set a good example. Drum band learning at  Hj. Isriati Baiturrahman 2 Semarang Kindergarten School is held twice a week, on Thursday and Friday. Drum band activities can train discipline, train cohesiveness, change learning patterns and habits, train leadership, train cooperation, change character, can motivate yourself, and train to socialize. In this study, it can be said that drum band learning already contains interpersonal intelligence, then drum band learning can be used as a medium to support children's interpersonal intelligence. Keywords: Drum band; Interpersonal Intelligence; Teacher's Strategy